'Native Foreigners' of Turkey: The Non-Muslim Minority as An Instantiation of Homo Sacer. Issue 4 (4th July 2021) - Tansuğ, Feryal
ABSTRACT: Non-Muslims of the Ottoman Empire took part in the nascent Turkish Republic with minority status in accordance with the Lausanne Treaty in 1923. The Law of Wealth Tax ( Varlık Vergisi ), as an exceptional law, was imposed on Turkish citizens between 1942 and1943 at the expense of non-Muslim Turkish nationals. Non-Muslims who could not pay the tax were taken to labour camps. Non-Muslims' treatment by the Turkish state generally has been discussed in terms of exclusion as 'foreigners', mentioning the racist elements in nation-state building process. But this article argues distinctly that their inclusive exclusion from the social space and political society produced what Giorgo Agamben calls 'bare life', wherein they were subjected to the violence of the sovereign as homo sacer s. It critically examines the problematic of sovereignty, using Agamben's analysis of sovereignty on power and its relationship to the state of exception, depending on the diary of a Greek Turkish citizen written in a labour camp.